GIANT MAGNETORESISTANCE (GMR): SPINNING FROM RESEARCH TO ADVANCED TECHNOLOGY - K.Y. Kok; I.K. Ng (Universitas Gadjah Mada, 2002)
In this paper, we aim to examine the research and development of materials demonstrating the giant magnetoresistance (GMR) property, a novel material property that has revolutionalised the advances of magnetic sensor and mass-memory technology today. A comprehensive outline for the fundamental materials aspects as well as the physics of the underlying mechanisms behind the GMR property is given. Recent development of GMR materials in data storage industry and other potential technological applications exploiting the GMR property are also discussed.